ANALYSIS OF MODERN RETAIL "TRENMU MART" IN IMPROVING ECONOMIC INDEPENDENCE - Izzuddin Syihab; Nurani Puspa Ningrum; Tuti’ Nadhifah (JURNAL PROFIT, 2025)
This study aims to analyze the role of the modern retailer Trenmu Mart in increasing the economic independence of the Muhammadiyah Kudus Islamic Boarding School. As Islamic educational institutions, Islamic boarding schools often face financial dependence on fluctuating Educational Development Contributions (SPP) and external aid, which impacts employee welfare and the implementation of student development programs. Efforts to create independent funding sources through business units were previously undertaken with the establishment of Mu Mart in 2016, but were unable to survive due to a lack of professional management and an unstrategic location. This experience led to the establishment of Trenmu Mart in 2025 as a new strategy to build the economic independence of Islamic boarding schools. This research employed a descriptive qualitative method, with data collection techniques including interviews, observation, and documentation. Data analysis was conducted through data reduction, presentation, and drawing conclusions, and its validity was tested using source and method triangulation. The research results show that Trenmu Mart has a positive impact on the economic independence of Islamic boarding schools. Sales have increased significantly every week since the start of operations, with profits used to improve employee welfare through incentives and allowances, and to support various student activities, such as providing learning resources, skills training, and religious programs. Furthermore, Trenmu Mart serves as a learning medium for entrepreneurship for students involved in store operations, providing real-world experience in Sharia-based business management practices. Trenmu Mart's presence also strengthens the relationship between Islamic boarding schools and the surrounding community, which also benefits economically through easy and affordable shopping access. The research conclusion confirms that Trenmu Mart serves not only as a commercial entity but also as a social, educational, and da'wah instrument. Its management concept aligns with the principles of social entrepreneurship in Islamic economics and reflects the application of the maqashid sharia principles in economic activities. With professional management and support from all elements of the Islamic boarding school, Trenmu Mart has long-term prospects as a model of Islamic boarding school economic independence that can be replicated in other Islamic educational institutions in Indonesia